Manu's code of law : a critical edition and translation of the Manava-Dharmasastra - Manu (Lawgiver) (South Asia research (New York, N.Y.), 2005)
Manu's Code of Law is one of the most important texts in the Sanskrit canon, indeed one of the most important surviving texts from any classical civilization. It paints an astoundingly detailed picture of ancient Indian life-covering everything from the constitution of the king's cabinet to the price of a ferry trip for a pregnant woman-and its doctrines have been central to Indian thought and practice for 2000 years. Despite its importance, however, until now no one has produced a critical edition of this text. As a result, for centuries scholars have been forced to accept clearly inferior ed.